Stimulatory role of the chemokine CCL2 in the migration and peptide expression of embryonic hypothalamic neurons. (16th August 2014) - Poon, Kinning; Ho, Hui T.; Barson, Jessica R.; Leibowitz, Sarah F.
Abstract Neuroinflammation is a feedback mechanism against infection, with recent studies suggesting a neuromodulatory role. The chemokine, (C‐C motif) ligand 2 (CCL2), and its receptor, (C‐C motif) receptor type 2 (CCR2), affect neuromodulation and migration in response to damage. Although CCL2 co‐localizes with neuropeptides in the hypothalamus that control voluntary behavior, the function of CCL2/CCR2 is unknown. This led us to consider the possibility that CCL2 acting through CCR2, under natural conditions, may affect the migration and peptide levels of hypothalamic neurons that control voluntary behavior. This study used primary embryonic hypothalamic neurons to examine the effect of CCL2 on migratory behavior and on levels of the peptides, enkephalin (ENK) and galanin. Treatment with CCL2 led to a significant, dose‐dependent increase in the number of migrated neurons and an increase in the velocity and distance traveled. CCL2 also significantly increased the number of ENK‐expressing and CCR2/ENK co‐expressing neurons and the percentage of neurons that contain higher levels of ENK. Lastly, CCL2 produced a dose‐dependent increase in expression of ENK and galanin. These results provide evidence for a stimulatory effect of CCL2 on embryonic hypothalamic neurons involving changes in migratory behavior, expression, and synthesis of neuropeptides that function in controlling behavior. <boxed-text content-type="graphic" id="jnc12827-blkfxd-0100" position="anchor" orientation="portrait"> </boxed-text> Our results demonstrate that the chemokine, CCL2, functions through its receptor, CCR2, to stimulate the migration and expression of the orexigenic peptides, enkephalin (ENK) and galanin (GAL), in developing embryonic hypothalamic neurons that are important for controlling ingestive behavior. This evidence reveals broad effects of CCL2 in the developing hypothalamus, showing this chemokine system to be tightly linked to the hypothalamic peptide neurons.